Innovation and Policy Support for Two-Sided Market Platforms: Can Government Policy Makers and Executives Optimize Both Societal Value and Profits? - Jung, Dawoon; Kim, Byung Cho; Park, Myungsub; Straub, Detmar W. (Information Systems Research, 2019)
A prime example of an emerging two-sided market is the driverless vehicle industry, an industry that will get much of its software from one side of the market: specifically, application developers. Consumers stand at the other side of this market. To what extent will this marketplace reward both the industry itself and application developers for technological innovation? In modeling this first question and keeping in mind consumers’ appetite for technological advances, we provide nuanced answers for executives in the driverless industry, application development firms, and government. This question speaks directly to what level of investment is optimal. Given that high government officials want to encourage the future growth of this vibrant industry, a second key theme of the paper is as follows. Should governments subsidize the focal industry or developers based on the extent to which they are innovative? Or should governments subsidize consumers? Our models conclude that subsidizing the industry is the overall best strategy followed by subsidies for consumers under certain other conditions. We find that it is not in the interest of society to subsidize application developers. Executives can use our models and results to fine tune to match their own circumstances with basic changes in our parameters.